2016
DOI: 10.1364/oe.24.022908
|View full text |Cite
|
Sign up to set email alerts
|

Suspended silicon mid-infrared waveguide devices with subwavelength grating metamaterial cladding

Abstract: We present several fundamental photonic building blocks based on suspended silicon waveguides supported by a lateral cladding comprising subwavelength grating metamaterial. We discuss the design, fabrication, and characterization of waveguide bends, multimode interference devices and Mach-Zehnder interferometers for the 3715 - 3800 nm wavelength range, demonstrated for the first time in this platform. The waveguide propagation loss of 0.82 dB/cm is reported, some of the lowest loss yet achieved in silicon wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(82 citation statements)
references
References 21 publications
1
81
0
Order By: Relevance
“…One strategy involves replacing the lossy silicon oxide cladding with other materials exemplified by silicon-on-nitride ( Figure 3A-B) [10] and germanium-on-nitride [17] or with air cladding in pedestal [11,18,19] or suspended silicon structures [12][13][14][20][21][22][23] (Figure 3C-H). Another option is Ge-on-Si (or SiGeon-Si), which claims the advantage of compatibility with Si CMOS processing, as high-quality Ge can be epitaxially grown on Si ( Figure 3I-J) [15,17,[24][25][26][27][28].…”
Section: Waveguides and Passive Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…One strategy involves replacing the lossy silicon oxide cladding with other materials exemplified by silicon-on-nitride ( Figure 3A-B) [10] and germanium-on-nitride [17] or with air cladding in pedestal [11,18,19] or suspended silicon structures [12][13][14][20][21][22][23] (Figure 3C-H). Another option is Ge-on-Si (or SiGeon-Si), which claims the advantage of compatibility with Si CMOS processing, as high-quality Ge can be epitaxially grown on Si ( Figure 3I-J) [15,17,[24][25][26][27][28].…”
Section: Waveguides and Passive Devicesmentioning
confidence: 99%
“…In all these cases, the accessible wavelength is bound by the Si material absorption at approximately 7-8 μm. For photonic devices operating at even longer wavelengths, alternative materials other than Reprinted with permission from [11], (D, E) schematic view and top-view SEM image of suspended Si mid-IR micro-ring resonators [12] (© 2013 Optical Society of America), the waveguides assume a ridge geometry and an undercut etch removes the silicon dioxide cladding through access holes on the slab layer, (F, G) SEM micrographs of a suspended mid-IR Si photonic crystal cavity [13] (© 2011 Optical Society of America), (H) suspended mid-IR Si waveguides with sub-wavelength grating (SWG) claddings [14] (© 2016 Optical Society of America); here the SWG provides both lateral optical confinement as well as access to the oxide under cladding during wet etch structure release; the arrows indicate light propagation direction in the suspended core. (I, J) Ge-on-Si [15] (© 2015 IEEE): (I) a mid-IR Ge-on-Si ridge waveguide; (J) TEM cross-sectional image of the Ge-on-Si film showing that the dislocations are confined at the Si/Ge interface.…”
Section: Waveguides and Passive Devicesmentioning
confidence: 99%
“…Since the first experimental demonstration of an optical waveguide with a subwavelength periodic core [4], these structures, also called subwavelength gratings (SWGs), have found many applications in integrated optics, for example as highly efficient fiber-chip couplers [3][4][5][6][7][8][9], low-loss waveguide crossings, evanescent field sensors [10,11], broadband directional couplers [12] and multimode interference (MMI) [13] couplers, polarization beam splitters [14][15][16], wavelength division [4] and mode division [17] multiplexers, delay lines [18], Fourier-transform spectrometers [19] and suspended (membrane) waveguides for mid-infrared applications [20]. Exhaustive reviews of SWG fundamentals and applications can be found in [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Passive photonic components need to be made from optically transparent materials in the mid-IR. Since silica becomes opaque at wavelengths longer than 4 μm, mid-IR integrated resonators demonstrated to date either involve special suspended designs [1][2][3][4][5][6][7][8][9] or new material platforms, such as silicon-on-sapphire [10][11][12][13][14][15][16], silicon-on-nitride [17][18][19][20], or germanium-on-silicon [21][22][23][24][25][26]. Active optoelectronic devices rely on narrow-bandgap semiconductors to enable operation at mid-IR wavelength, although lattice mismatch of these semiconductors generally prohibit their epitaxial growth and integration on silicon, and therefore heterogeneous integration of III-V semiconductors or graphene have been demonstrated as an alternative route to resolve the challenge [27][28][29][30].…”
Section: Integrated Photonics For Infrared Spectroscopic Sensingmentioning
confidence: 99%